Financing Customer Default Risk Control System at BMT Amanah Ummah Surabaya - Abdul Majid Toyyibi; Amelia Ningsih; Faisol Lurrohman (Journal on Education, 2023)
An Islamic financial institution such as BMT Amanah Ummah hopes for soundness in financing its customers, but the running of financing activities certainly emphasizes that technical rules must be implemented so that default problems will occur so that risk control is the main thing for BMT analysts. The purpose of this study is to determine the BMT risk control system in the occurrence of the risk of default on financing customers. While this research is a type of field research which then uses qualitative research as its approach. In order to get credible results, the researchers carried out data collection techniques, data analysis to the validity of the data. The results of his research are that an BMT Amanah Ummah analyst puts forward the precautionary principle as initial control because it is the main basic part that must be considered besides also having to review based on the character of the customer.